Taqābuḍ Ḥukmī in Crypto Asset Transactions: Digital Ownership under Islamic Law in Aceh’s Sharia Financial Context - Istianah Zainal Asyiqin; M. Fabian Akbar; Muhammad Daffa Auliarizky Onielda (Jurnal Ilmiah Al-Syir'ah, 2026)
This study analyzes taqābuḍ ḥukmī in crypto asset transactions within Aceh’s sharia financial context. The rise of crypto assets raises a key question in fiqh muamalah: how can Islamic law recognize ownership and possession when the object is non-physical and exists through blockchain records, wallets, and private keys? Unlike studies that focus mainly on whether cryptocurrency is halal or haram, this article examines digital ownership and constructive possession in a setting where sharia financial norms have formal legal significance. By examining taqābuḍ ḥukmī in blockchain-based transactions, this study presents crypto assets as a case of how Islamic law adapts its doctrines of property and possession to contemporary socio-legal and technological change. Using a normative-doctrinal legal approach with a contextual socio-legal reading, the study examines classical fiqh doctrines, contemporary sharia standards, Indonesian regulations, Aceh’s sharia financial framework, academic literature, institutional fatwas, and expert opinion. The study finds that crypto assets may be categorized as māl mutaqawwam when they have lawful utility, economic value, scarcity, technological infrastructure, and market recognition. However, valid crypto transactions depend not only on the asset’s status but also on the transaction mechanism. Spot transactions may fulfill taqābuḍ ḥukmī when buyers obtain effective digital control through wallet access, blockchain confirmation, private-key control, or transferability. Futures trading, leverage, short selling, fixed-yield schemes, and manipulative practices remain problematic because they may involve riba, gharar, maysir, najasy, or unlawful consumption of wealth. This article develops an Acehnese sharia digital ownership framework for assessing crypto transactions within Islamic economic law in Aceh.